Kinetics Study of Paracetamol Production from Para-Aminophenol and Acetic Anhydride - Rifki Wahyu Kurnianto; Muhammad Fahrurrozi; Hilda Ismail; Raden Rara Endang Lukitaningsih; Indah Tri Nugraha; Pudjono Pudjono; Rochmadi Rochmadi; Ari Sudarmanto; Ratna Asmah Susidarti (Jurnal Rekayasa Proses, 2021)
In the last decade, Indonesia intensifies the efforts to reduce pharmaceutical imports. One of the initiatives is establishing a paracetamol production facility to start operating in 2024. Kinetics study is needed as a basis to design the paracetamol reactor. This study investigated the optimal temperature, reactant mole ratio, and agitation speed in the reactor for paracetamol production. In this study, aqueous solution of para-aminophenol was reacted with acetic anhydride. The mole ratio of para-aminophenol to acetic anhydride was varied to 1:1, 1:1.2, 1:1.5, and 1:2 while the temperature was varied to 80 °C, 90 °C, and 110 °C. However, due to uncontrolled heat of the reaction and limitation of the mixture’s boiling point, the actual reaction temperatures were 86 °C, 90 °C, and 108 °C. In addition, the agitation speed of 250 RPM and 350 RPM were also studied. Thin layer chromatography (TLC) and densitometry were used to determine the concentration of paracetamol in the reacting mixture. The optimum temperature, reactant mole ratio, and agitation speed in this study were 108 °C, 1:1.5, and 350 RPM, respectively. In addition, a reaction performed under those operating parameters gave the reaction rate constant of 1.95 L mol-1 min-1.Keywords: acetic anhydride; kinetics; para-aminophenol; paracetamol; pharmaceutical industry A B S T R A KDalam sepuluh tahun terakhir ini, Indonesia bertekad mengurangi impor bahan baku farmasi. Salah satu upaya yang dilakukan adalah membangun fasilitas produksi parasetamol yang akan mulai beroperasi pada tahun 2024. Studi kinetika diperlukan sebagai dasar perancangan reaktor parasetamol. Oleh karena itu, penelitian ini mengkaji kondisi operasi optimal pada reaksi produksi parasetamol yang akan dibutuhkan sebagai dasar perancangan pabrik. Pada percobaan ini, para-aminofenol direaksikan dengan anhidrida asetat dengan media air. Rasio mol para-aminofenol terhadap asetat anhidrida divariasikan 1:1 1:1,2, 1:1,5, dan 1:2 sedangkan temperatur divariasikan 80 °C, 90 °C, dan 110 °C. Akan tetapi, karena panas reaksi yang tidak dikontrol dan batasan berupa titik didih dari campuran reaksi, temperatur aktual reaksi menjadi 86 °C, 90 °C, dan 108 °C. Selain itu, kecepatan putaran pengadukan juga divariasikan pada angka 250 RPM dan 350 RPM. Kromatografi lapis tipis (KLT) dan densitometri digunakan untuk menentukan konsentrasi parasetamol dalam campuran reaksi. Temperatur, rasio mol reaktan, dan kecepatan putaran pengadukan yang optimum pada penelitian ini masing-masing adalah 110 °C, 1:1,5, dan 350 RPM. Selain itu, reaksi yang dilakukan dengan kondisi operasi tersebut menghasilkan konstanta laju reaksi 1,95 L mol-1 menit-1.Kata kunci: anhidrida asetat, industri farmasi, kinetika, para-aminofenol, parasetamol